2021
DOI: 10.23989/gerontologia.100584
|View full text |Cite
|
Sign up to set email alerts
|

Muistisairauteen sopeutumisen tarinatyypit työikäisenä sairastuneilla ja heidän läheisillään

Abstract: Työikäisenä muistisairauteen sairastuminen rikkoo oletetun elämänkulun, vaatien sopeutumista ja elämäntarinan uudelleenrakentamista. Tutkimuksessa selvitettiin työikäisenä sairastuneiden ja heidän läheistensä haastatteluiden (n = 26) perusteella, kuinka sairastuneet jäsentävät muistisairauden aiheuttamia elämänmuutoksia sai­rauden alkuvaiheessa ja miten läheisen tarina resonoi sairastuneen tarinan kanssa. Analyysissä havaittiin kolme erilaista tarinatyyppiä. Kaaoksen tarinaa leimasi sairas­tumisen aiheuttama e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 30 publications
0
3
0
2
Order By: Relevance
“…The aim of this article was to discover how the family members readjust to YOD as being a part of their everyday life during the first four years from the onset of the illness. By narrating their own situation, talking about their relationship with the person with YODs and the impact on their daily living, the family members were able to reconstruct their own story about their relationship as well as their own coping, abilities and burdens (see Frank, 1995;Hautsalo et al, 2021). The analysis uncovered broken, adaptive or alternative storylines.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The aim of this article was to discover how the family members readjust to YOD as being a part of their everyday life during the first four years from the onset of the illness. By narrating their own situation, talking about their relationship with the person with YODs and the impact on their daily living, the family members were able to reconstruct their own story about their relationship as well as their own coping, abilities and burdens (see Frank, 1995;Hautsalo et al, 2021). The analysis uncovered broken, adaptive or alternative storylines.…”
Section: Discussionmentioning
confidence: 99%
“…Family members differ in their attempts to manage in the new life situation and they readjust in individual ways. Early narrative research on illness-related experiences have reported cultural storylines (Frank, 1995;Freeman, 2008;Hautsalo et al, 2021) and strategies to manage in difficult situations (Baltes & Rudolph, 2012;Frankl, 1979). Independent stories are always individual and may consist of features from different storylines that vary according to the related context and changes in the narrator's life situation.…”
Section: The Changes Made By a Yod In The Family's Situation And Atte...mentioning
confidence: 99%
See 1 more Smart Citation
“…Aikaisemmat tutkimuksemme puolestaan osoittavat, että jopa syvästi muistisairaiden ikääntyneiden eksistentiaalisiin ja hengellisiin tarpeisiin on mahdollista vastata (Saarelainen ym. 2020;Pirhonen 2021). Hoivakodeissa asuvista ihmisistä valtaosa onkin muistisairaita (Remes 2018).…”
Section: Johdantounclassified
“…2018;Agli ym. 2019), mutta hengellisyyden ammattilaiset harvemmin (Carey 2012;Pirhonen 2021;Pirhonen & Saa relainen 2022). Lisäksi valtaosa hoitolaitos pappien työtä koskevasta tutkimuksesta sijoittuu terveydenhuollon yksiköihin eikä ikäihmis ten asumispalveluihin (Proserpio ym.…”
Section: Johdantounclassified